Genre-Based Approach for Better Recount Writing in the Classroom (Jurnal Pelangi : Research of Education and Development, 2023)
The purpose of this study is to see if there are any variations in students' writing abilities before and after using a genre-based approach, and how to improve students' writing skills in studying recount text using a genre-based approach. This study is a single-subject experimental study. The data collection instrument was a test of students' writing abilities in the form of recount text. The sample size in this study was 15 participants, from class X TKJ 3. The paired t-test and the N-gain technique were used to analyze data from students' writing assignments. Based on data analysis utilizing the paired sample t-test, it was determined that students' writing talents differed before and after applying the genre-based approach. The N-Gain test findings indicate that students' writing abilities improved significantly after adopting a genre-based approach to recount text content.